Synergistic Effect of Low Doses of Tumor Necrosis Factor and Sera from Patients with Systemic Lupus Erythematosus on the Expression of Procoagulant Activity by Cultured Endothelial Cells - Hasselaar, Paula; Derksen, Ronald H W M; Oosting, Janine D; Blokzijl, Laya; de Groot, Philip G (Thrombosis and Haemostasis, 1989)
The effect of 15 antiphospholipid antibody (APA) positive SLE sera, 13 APA negative SLE sera, 10 APA negative sera from patients with other connective tissue diseases (CTD) and 15 control sera on the expression of endothelial procoagulant activity (PCA) was studied. Endothelial cells (EC) were stimulated with tumor necrosis factor (TNF) and 20% serum for 4 hr and the surface PC A expression was measured. Without TNF, none of the sera stimulated PC A expression. With subop timal TNF stimulation, 14/15 APA positive SLE sera, 7/13 APA negative SLE sera, 2/10 CTD sera and 2/15 control sera enhanced PC A expression. This stimulating effect resided in the IgG fraction and was associated with the presence of APA, but not with a history of thrombosis. Purified APA had no PC A stimulating activity. PC A expression was inhibited by cycloheximide and heat treatment (30 min, 56° C) of serum.In conclusion, 21/28 (75%) SLE sera increase the TNF-induced endothelial PC A expression. Although this effect predominantly occurs with APA positive serum, a causative role of APA was not demonstrated.
Keywords: Antiphospholipid antibodies; Systemic lupus erythematosus; Procoagulant activity